Long-term results of cervical disc arthroplasty: a single-center retrospective study with a minimum 10-year follow-up - He, Junbo; Li, Yaling; Shen, Yiwei; Wang, Xingjin; Yan, Lu; Wu, Tingkui; Ding, Chen; Liu, Hao (Journal of neurosurgery. Spine, 2025)
OBJECTIVE This study aimed to retrospectively evaluate the long-term clinical and radiological outcomes following cervical disc arthroplasty (CDA). METHODS This study included 74 patients who underwent single- or two-level CDA between November 2004 and December 2013, with a minimum 10-year follow-up (22 in the Bryan disc group and 52 in the Prestige LP disc group). Patient-reported outcomes and radiological parameters were collected for comparisons. Additionally, the incidences of heterotopic ossification (HO), adjacent segment degeneration (ASD), prosthesis subsidence, and segmental kyphosis at the final follow-up were evaluated and analyzed. A 95% confidence interval (CI) for a mean difference or odds ratio (OR) was used for all general statistical calculations. RESULTS After 10 years of follow-up, patients with CDA continued to show significant improvement from baseline in patient-reported outcomes (p < 0.001), with no significant differences between the two groups. However, the Bryan disc group had significantly higher global range of motion (ROM; 95% CI 4.8°-19.2°, p = 0.001) and segmental ROM (95% CI 1.3°-5.9°, p = 0.003) compared to the Prestige LP disc group. At 10 years postoperatively, the incidence of HO was 69.2%, including 29.7% ROM-limiting HO. The incidence of ASD was 55.4%. Segmental kyphosis was observed in 10 patients, with a 20.8% incidence in the Bryan disc group and an 8.1% incidence in the Prestige LP disc group (p = 0.072). In the univariate subgroup analysis, the age of the ASD group was significantly higher (95% CI 0.3-6.8, p = 0.034). However, no statistically significant parameters were identified between the HO and non-HO groups. CONCLUSIONS Through at least 10 years of follow-up, CDA can achieve satisfactory clinical outcomes while effectively preserving segmental mobility.
Veröffentlicht: 06. Juni 2025
Gesehen am 12.01.2026